Pengaruh Penerapan Metode Demonstrasi Terhadap Keterampilan Berhitung Siswa Kelas 3 SD Negeri Kecandran 01 - Fitriyah, Lailatul; Purba, Romirio Torang (LPPM Undiksha, 2017)
The purpose of this research is to know the influence of the implementation of demonstration method to the numeracy skills of third grade students of SDN Kecandran 01 in second semester of academic year 2016/2017. This research is an experimental research. This research was conducted in two different schools namely SDN Kecandran 01 in class 3 as the experimental class and SDN Dukuh 01 in class 3 as the control class. Students of each school in class 3 as many as 32 students. Data analysis technique used in this research is ancova test using unvariet. The results showed that in the experimental class average pretest of 50, for the average posttest value of 88.59. While in the control class the average pretest value of 48.13, for the posttest value of 79.69. The difference in the pretest value of the two classes was 1.87, while the difference in the posttest average was 8.9. So it can be concluded that there is influence of the implementation of demonstration methods on the numeracy skills of third grade students of SDN Kecandran 01 Salatiga in the second semester of academic year 2016/2017.